Factors associated with malaria infection among children after distribution of PBO-pyrethroid synergist-treated nets and indoor residual spraying in north-western Tanzania. - Ummi Abdul Kibondo; Jenny Renju; Eliud Lukole; Jacklin F Mosha; Franklin W Mosha; Alphaxard Manjurano; Mark Rowland; Natacha Protopopoff (PLoS ONE)
Background After a decade of successful control, malaria is on the rise again. The prevalence of malaria in Tanzania has increased from 7% in 2017 to 8% in 2022 and reached 18% in Kagera region in the North West of Tanzania. Malaria vectors in Muleba district Kagera have high level of pyrethroid resistance. The aim of this paper is to explore factors associated with malaria infection prevalence in children aged 6 months to 14 years in Muleba, where Long Lasting Insecticidal Net (LLIN) combining a pyrethroid insecticide and synergist piperonyl butoxide (PBO) that counteract resistance in the mosquitoes, was first distributed under trial conditions in 2015. Methods The trial was a community randomized control in which there were two malaria prevalence cross-sectional household surveys each year (June and December) from 2015 to 2017 in Muleba. In this study we conducted a secondary data analysis of the December surveys only. Multilevel Poisson regression analysis was used to assess factors associated with malaria infection. Results A total of 10,941 children and 4,611 households were included in this study. Overall malaria prevalence was 35.8%, 53.3% and 54.4% in the year 2015, 2016 and 2017 respectively. Living in an area with standard LLIN as opposed to the novel PBO synergist LLIN, being a male child, above 5 years of age, living in a house with open eaves, living in house without IRS, having head of household with no formal education, lower socioeconomic status and survey year were associated with increased risk of malaria infection. Conclusions Using PBO LLIN reduced the risk of malaria infection. However, additional measures could further reduce malaria infection in areas of insecticide resistance such as housing improvement.